Air pollution and blood pressure in the elderly: evidence from a panel study in Nanjing, China. Issue 9 (September 2022) - Lin, Yang-Chi-Dung; Cai, Yutong; Huang, Hsi-Yuan; Liang, Donghai; Li, Jing; Tang, Yun; Hong, Hsiao-Chin; Yan, Qiting; Huang, Hsien-Da; Li, Zhaoyuan
Abstract: Background: Air pollution is known to have notable negative effects on human health. Recently, the effect of air pollution on blood pressure among the elderly has attracted researchers' attention. However, the existing evidence is not consistent, given that positive, null, and negative outcomes are presented in the literature. In this study, we investigated the relationship between blood pressure (BP) and indices of air pollutants (PM2.5, PM10, and air quality index) in a specific elderly population through a panel study to address this knowledge gap. Methods: We obtained repeated BP measurements from January 2017 to May 2019 in a panel of 619 elderly with a total of 5106 records in Nanjing, China. Data on daily indices of ambient air pollutants, including fine particulate matter with an aerodynamic diameter of ≤ 2.5 μ m (PM2.5 ), ≤ 10 μ m (PM10 ), and air quality index (AQI) of the same period were obtained. We evaluated the association between BP and average concentrations of air pollutants in the past one-week, two-week, and four-week lags before measuring the BP. The non-linear panel regression models were used with fixed- and mixed-effects to control age, gender, and temperature. Results: In the non-linear panel fixed-effects model, the average concentration of PM2.5 is significantly associated with systolic BP (SBP) at all lags but is only significantly correlated with diastolic BP (DBP) at a one-week lag. An interquartile range (IQR) increase of one-week average moving PM2.5 (38.86 μg/m 3 ) of our sample increases the SBP and DBP by 7.68% and 6.9%, respectively. PM10 shows the same pattern of effect on BP as PM2.5 . AQI shows less significant associations with BP. In the non-linear mixed-effects model, the average concentrations of PM2.5 and PM10 are significantly associated with SBP at all lags but have no significant effect on DBP at one- and two-week lags. AQI is only significantly associated with DBP at a one-week lag. Conclusions: Exposures to ambient particulate matter (PM2.5 and PM10 ) were associated with increased BP among older people, indicating a potential link between air pollution and the high prevalence of hypertension. Air pollution is a well-recognized risk factor for future cardiovascular diseases and should be reduced to prevent hypertension among the elderly. Abstract : Air pollution; Panel study; Elderly population.